Human Sigma Optimization: Improving Employee Engagement - ALRASHID, ENCE RAMLI (Jurnal Muara Ilmu Ekonomi dan Bisnis, 2018)
Competition in banking industry from year to year increasingly fierce. Small capital banks must open compete with large banks in the same segment. Local banks must compete "apple to apple" with other local banks. In addition, local bank has to be able to compete with foreign banks in order to gain the largest market share. The level of customer engagement can be a leading indicator at the rate of return for investors. It means if the CE survey results produce a high level of engagement, then the company's financial performance expectation is also high. employee engagement level is the basic indicator of leading indicators. It means that if the EE survey results produce a high level of engagement then, engagement costumer is also high on products or services owned by a bank. Human Sigma is a model and approach by analyzing the value of Customer Engagement and Employee Engagement to determine Human Sigma Value that will describe the level of engagement from the point of view of employee and customer. The aim of this study is to look for top of pain factors the weakness of employee engagement in the retail banking company that caused the decrease of customer engagement and the level of company productivity by using the concept of human sigma.